If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 + -1(-3 + -2g) + -10 = 0 -7 + (-3 * -1 + -2g * -1) + -10 = 0 -7 + (3 + 2g) + -10 = 0 Reorder the terms: -7 + 3 + -10 + 2g = 0 Combine like terms: -7 + 3 = -4 -4 + -10 + 2g = 0 Combine like terms: -4 + -10 = -14 -14 + 2g = 0 Solving -14 + 2g = 0 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 2g = 0 + 14 Combine like terms: -14 + 14 = 0 0 + 2g = 0 + 14 2g = 0 + 14 Combine like terms: 0 + 14 = 14 2g = 14 Divide each side by '2'. g = 7 Simplifying g = 7
| 7-5x=27 | | b^4=48 | | 4x+4(x+9)=20 | | y^2-10y+2x+25=0 | | (5a^3+6a)+(-3a^2-5a)= | | 2m-14=6 | | 5(3x+7)-(4x-6)=12 | | 5k-13=2k+2 | | (4+3x+x^2)+(6-9x+x^2)= | | 4t+9=-9t-13 | | -3(1+w)+4w=8 | | -6x+36=28 | | 8-(2x-6)=22 | | 4+8y+9n-2y-2n-17= | | -p^2+8p+4= | | 4z+3(z+7)=-14 | | 2(x-2y-7z)= | | -4p^3+32p^2+16p= | | 2(9x-8)= | | 2(a+5)-a=-7 | | 3y+14=13 | | 5x(x-6)= | | 3a(a+2)= | | 4+2*n=10 | | ln(8x-1)=5 | | d^2-8d+4=0 | | 18-4*2=l | | p(p-8)= | | 18-4*2=k | | 3x+6=-45 | | 5*c=78 | | 2w+2(4w)+w=329 |